Gandhians' rise to power: National movement, power politics & independence (1920-47 AD) - Pradhan, Prasant Kumar (New Delhi Commonwealth, 2024)
On the freedom movement in Orissa, with reference to Gandhian movement.
Keywords: Mahatma Gandhi; National Movement